THE EFFECT OF WILLINGNESS TO CHANGE, JOB SATISFACTION, AND INTERHUMAN RELATIONS ON EMPLOYEE PERFORMANCE AT PT. LMN, PASURUAN REGENCY - Orell Xalansa Ludbiyanto; Ika Korika Swasti; Sugito Sugito (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the influence of readiness for change, job satisfaction, and interpersonal relationships on employee performance at PT. LMN. A quantitative research design was employed, involving 128 employees as research respondents. Data were analyzed using linear regression to assess the relationships among the variables. The findings indicate that readiness for change, job satisfaction, and interpersonal relationships each have a positive and significant effect on employee performance. Employees who demonstrate greater adaptability to organizational changes tend to exhibit higher levels of productivity. Similarly, higher job satisfaction is associated with enhanced work engagement and performance outcomes. In addition, positive interpersonal relationships within the workplace contribute to improved performance through effective communication and social support. These results underscore the importance of fostering adaptability, maintaining employee satisfaction, and promoting healthy workplace relationships as key drivers of optimal organizational performance. Keywords: Willingness to Change; Job Satisfaction; Interhuman Relations; Employee Performance